2021
DOI: 10.3389/fcvm.2021.719160
|View full text |Cite
|
Sign up to set email alerts
|

Near Complete Repair After Myocardial Infarction in Adult Mice by Altering the Inflammatory Response With Intramyocardial Injection of α-Gal Nanoparticles

Abstract: Background: Neonatal mice, but not older mice, can regenerate their hearts after myocardial-infarction (MI), a process mediated by pro-reparative macrophages. α-Gal nanoparticles applied to skin wounds in adult-mice bind the anti-Gal antibody, activate the complement cascade and generate complement chemotactic peptides that recruit pro-reparative macrophages which are further activated by these nanoparticles. The recruited macrophages decrease wound healing time by ~50%, restore the normal skin structure and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…Galili et al utilized α-gal nanoparticles prepared from rabbit red blood cell membranes to recruit pro-reparative macrophages to the infarcted territory in a mouse model of myocardial infarction. After 28 days of treatment, treated mice demonstrated a marked remission in terms of infarct size (~ tenfold smaller), restoration of normal myocardium structure and contractile function comparing with control group [ 44 ]. Such strategy has also been applied to manage diabetic wound healing with satisfying outcomes [ 45 ].…”
Section: The Interaction Between Nps and The Immune Systemmentioning
confidence: 99%
“…Galili et al utilized α-gal nanoparticles prepared from rabbit red blood cell membranes to recruit pro-reparative macrophages to the infarcted territory in a mouse model of myocardial infarction. After 28 days of treatment, treated mice demonstrated a marked remission in terms of infarct size (~ tenfold smaller), restoration of normal myocardium structure and contractile function comparing with control group [ 44 ]. Such strategy has also been applied to manage diabetic wound healing with satisfying outcomes [ 45 ].…”
Section: The Interaction Between Nps and The Immune Systemmentioning
confidence: 99%
“…After LAD ligation followed by three-day tail vein injection of nanoparticles, given to the CD11b, CD44, and αLβ2-integrin combined on the surface of apoptotic bodies, the nanoparticles had the capability to target cardiac inflammation actively, thus promoting the M2 polarization and improving cardiac functions. Another interesting result came from Galili et al., 116 who used α-Gal nanoparticles that recruited macrophages via the activation of the complement system, whereas the accumulated macrophages showed an M2 phenotype and expressed high levels of VEGF, IL-1α, FGF, and PDGF, all reparative cytokines, thus decreasing the poor fibrosis and improved cardiac functions.…”
Section: Nanomaterials For the Regulation Of Immune Responsementioning
confidence: 99%
“…These observations raised the possibility that injection of α-gal nanoparticles into the post-MI injured myocardium of adult anti-Gal–producing mice may recruit macrophages that are activated to have the capacity of neonatal macrophages for mediating restoration of the normal structure and of contractility in the myocardium without scar formation. Studies in anti-Gal–producing GT-KO mice ( Galili et al, 2021 ) have demonstrated that ischemia in the adult mouse heart due to occlusion of the mid-left descending coronary artery for 30 min, followed by reperfusion, results in fibrosis and scar formation in ∼20% of the left ventricle myocardium including thinning of the ventricular wall (representative example in Figure 10A ). However, injection of α-gal nanoparticles into the injured myocardium immediately after reperfusion decreases the fibrosis to only ∼2% of the left ventricle due to infiltration of pro-reparative macrophages into the injured myocardium and its subsequent repopulation with healthy cardiomyocytes (representative example in Figure 10B ).…”
Section: Immunological Processes Associated With Anti-gal/α-gal Epitope Interactions Which May Be Harnessed For α-Gal Therapiesmentioning
confidence: 99%
“…However, injection of α-gal nanoparticles into the injured myocardium immediately after reperfusion decreases the fibrosis to only ∼2% of the left ventricle due to infiltration of pro-reparative macrophages into the injured myocardium and its subsequent repopulation with healthy cardiomyocytes (representative example in Figure 10B ). Thus, the post-MI α-gal nanoparticles treatment resulted in near complete restoration of the normal structure and function of the injured myocardium ( Galili et al, 2021 ).…”
Section: Immunological Processes Associated With Anti-gal/α-gal Epitope Interactions Which May Be Harnessed For α-Gal Therapiesmentioning
confidence: 99%
See 1 more Smart Citation